Web Service implementation using Blockchain Technology in Healthcare for discovery - Bhole, Gajanan; Devale, Prakash (Journal of Neonatal Surgery, 2025)
Blockchain technology has transformed traditional methods and gained wide recognition for its disruptive potential in various industries. Blockchain emerges as a promising beacon in healthcare where safeguarding data integrity, ensuring seamless data exchange and protecting patient privacy are critical priorities This paper is dedicated to multifaceted blockchain technology, benefits, barriers and emerging opportunities in the healthcare sector will be explored Through careful research, real-world case studies, and practical insights, paper seeks to provide a comprehensive understanding of how blockchain is poised to redefine healthcare operations, improve patient care, and transform the industryare majorly used in the treatment of this ailment. However more research and large sample size is required for the assessment of management of the following